FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KETERLAMBATAN PENANGANAN KANKER PAYUDARA STADIUM III &IV DI POLIKLINIK ONKOLOGI RSUD PROVINSI NTB 2018: Factors Associated with Delay Management of Stage III & IV Breast Cancer Treatment at The Oncology Polyclinic of The NTB Provincial Hospital 2018 - Misroh Mulianingsih; Ilham Ilham; Irwan Hadi; Meyka Aris Yusron; Zuliardi Zuliardi; Dwitya Citta P; Hayana Hayana (LPPM STIKES Pemkab Jombang, 2021)
ABSTRACT The breast is the most common organ for cancer in women. This study aims to determine the factors associated with managing treatment delays in patients with breast cancer stage III & IV at the NTB Provincial Hospital in 2018. The study design was a retrospective correlational analysis with a sample size of 35 people. They conducted at the Oncology Polyclinic of the NTB Provincial Hospital in January 2019 by using a questionnaire. Based on the study results, know that delays occurred in respondents with elementary education as many as 11 (31.4%) with 21 (60%) socio-economic incapacity criteria. Respondents who had sufficient psychology were 29 (82.8). Respondents who received referrals ? 30 days from the examination were 18 (51.4%), and respondents who received a diagnosis of ? 30 days were 25 (71.4%). Respondents who received referrals ? 30 days from the examination were 21 (60%), respondents who received first chemotherapy ? 20 days from diagnosis were 29 (82.9%), and respondents who received time ranges from first chemotherapy to second chemotherapy ? 30 days were 26 ( 74.3%). Recommendations that can give are to do socialization/counselling to the public about this breast cancer.